Manfaat Terapi Akupresur Terhadap Penurunan Kadar Gula Darah Pada Pasien DM Tipe II di Poliklinik Rumah Sakit Umum Imelda Pekerja Indonesia Medan - Meriani Herlina; Noradina Noradina; Bernita Silalahi; Paskah Rina Situmorang; Arta Marisi Dame; Candra Meriani Damanik; Satriani H Gultom; Yuni Shanti Ritonga; Syahrul Handoko Nainggolan; Ali Asman Harahap (Lembaga Pengabdian Masyarakat Universitas Ichsan Gorontalo, 2025)
Diabetes Mellitus (DM) is a chronic disease in the form of a metabolic disorder characterized by blood sugar levels that exceed normal limits. Diabetes Mellitus is known as a silent killer because it is often not realized by the sufferer and when it is known, complications have occurred. The method used in this research is the Quasy Experiment method using a pre-test and post-test approach with control group design. The population in this study was 40 respondents and the sample in this study was 20 respondents who were taken by purposive sampling. And analyzed Univariate and Bivariate using the Wilcoxon and Mann Whitney tests to determine the differences between the two groups on the effect of acupressure therapy. The results showed that the effect of acupressure therapy on reducing blood sugar levels was p-value = 0.005 <0.05 it can be concluded that there is an effect of acupressure therapy on reducing blood sugar levels in Type II DM patients at the Poliklinik Rumah Sakit Umum Imelda Pekerja Indonesia Medan. It is suggested that the results of this study are expected to be information for diabetes mellitus patients to independently carry out acupressure therapy and for the Indonesian Imelda Workers Hospital to include elements of acupressure therapy as study material in the management of type 2 diabetes mellitus patients.